Impact event and orofacial pain amid the COVID-19 pandemic in Brazil: a cross-sectional epidemiological study - DE Caxias, Fernanda Pereira [UNESP]; Athayde, Flávia Regina Florencio de [UNESP]; Januzzi, Marcella Santos [UNESP]; Pinheiro, Larissa Viana [UNESP]; Turcio, Karina Helga Leal [UNESP] (FapUNIFESP (SciELO), 2021)
OBJECTIVES: This study aims to assess the impact of social isolation, due to the Covid-19 pandemic, on mental health, Temporomandibular Disorder (TMD) and orofacial pain in men and women. METHODOLOGY: Individuals living in Brazil answered an online questionnaire on their sociodemographic and behavioral aspects, emotional scale (DASS-21), Impact of Event Scale, and Pain Screener in Temporomandibular Disorders (TMD-Pain Screener) during June 2020. Descriptive statistical analyses and logistic and linear regressions were applied (5% significance). RESULTS: Overall, 2301 individuals were included, 89.1% practiced social isolation, 72.6% were employed/studying, at least 15% presented severe or extremely severe levels of emotional distress and presence of powerful (34.1%) and severe impact event (15%). During the outbreak, 53.2% perceived feeling worse and 31.8% reported that orofacial pain started or worsened after the pandemic outbreak. Gender was associated with social class (P=0.036), pain/stiffness in the jaw on awakening (P=0.037), change of pain during jaw habits (P=0.034) and perception of change in the situations mentioned in the TMD-Pain Screener (P=0.020), depression (P=0.012), anxiety (P=0.006) and impact of the event (P=8.3E-11). Social isolation had a lesser chance to change the routine, to be practiced by the unemployed/not studying, and to be practiced by men (all with P<0.001). Associations were found between social class and all subscales of the DASS-21 and IES, all with P<0.001. CONCLUSIONS: The practice of social isolation has social determinants. High levels of psychological and event impacts were detected. The presence of orofacial pain seemed to increase during the health crisis, and there were gender differences in the response to the COVID-19 pandemic.